Toner, two-component developer, image forming apparatus, and toner manufacturing method

JP7629814B2Active Publication Date: 2025-02-14SHARP KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021113025
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-07
Publication Date
2025-02-14
Estimated Expiration
2041-07-07

AI Technical Summary

Benefits of technology

【0015】 本発明によると、外添剤としてチタン酸ストロンチウムの微粉体とシリカ粒子とを含有するトナーにおいて、環境帯電性能の向上と感光体ドラムへの研磨性の抑制とを両立できるトナー、二成分現像剤、画像形成装置及びトナーの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629814000002
    Figure 0007629814000002
  • Figure 0007629814000003
    Figure 0007629814000003
  • Figure 0007629814000004
    Figure 0007629814000004
Patent Text Reader

Abstract

To provide a toner that contains fine powder of strontium titanate and silica particles as an external additive, and can achieve both an improvement in environmental electrification performance and prevention of abrasion of a photoreceptor drum, a two-component developer, an image forming apparatus, and a method for manufacturing toner.SOLUTION: In a toner, an external additive is attached to the surface of a toner particle having a softening point of 110°C or less. The toner particle includes a crystalline polyester resin and wax. The external additive contains fine powder obtained by hydrophobing the surface of a composition including strontium titanate and silica with a silane compound, and silica particles. The number average equivalent circle diameter of primary particles of the fine powder is 20 nm or more and 50 nm or less. The number average equivalent circle diameter of primary particles of the silica particles is 50 nm or more and 200 nm or less.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner, a two-component developer, an image forming apparatus, and a method for producing a toner. [Background technology]

[0002] Toner (toner for developing electrostatic images) used in image forming devices such as electrophotographic copying machines, multifunction machines, printers, and facsimile machines usually has an external additive attached to the surface of the toner particles. In the external addition step in the toner manufacturing method, the toner particles and the external additive are mixed in a powder mixer such as a Henschel mixer to attach the external additive to the surface of the toner particles (hereinafter, also simply referred to as "externally adding").

[0003] The charge control agent is an external additive added to control the chargeability of the toner. Toners containing strontium titanate as a charge control agent have been known for some time, and the use of strontium titanate as a charge control agent improves the environmental charge performance of the toner. Here, the environmental charge performance of the toner refers to a small difference in the amount of charge of the toner between a high humidity environment and a low humidity environment, and by improving this performance, it is possible to print with a stable image density regardless of the surrounding environment of the image forming apparatus, and also to reduce image noise.

[0004] On the other hand, strontium titanate has a problem that it is difficult to disperse on the surface of toner particles because of its angular shape. In non-low-temperature fixing toners in which the softening point of the toner particles exceeds 110°C, strontium titanate can be sufficiently dispersed by mixing in a powder mixer for a long time as shown in the comparison of Figures 1 and 2. However, in low-temperature fixing toners in which the surface of the toner particles is soft (toners in which the softening point of the toner particles is 110°C or less), strontium titanate is embedded in the surface of the toner particles as shown in Figure 4 when mixed for a long time, and sufficient environmental charging performance cannot be achieved. In addition, as shown in Figure 3, if the mixing is performed for a short time, strontium titanate is not completely dispersed on the surface of the toner particles and aggregates are formed, so sufficient environmental charging performance cannot be achieved. In addition, the presence of the aggregates of strontium titanate, which has an angular shape, on the surface of the toner particles increases the abrasiveness to the photoconductor drum, and the film on the photoconductor drum is quickly worn down. In order to reduce the probability of strontium titanate appearing on the outermost surface of the toner, large silica particles can be added as a spacer to suppress film loss to some extent, but if the mixing time in the external addition process is extended to fully disperse the silica particles, the strontium titanate will be embedded in the surface of the toner particles, and the silica particles will fall into the depressions on the surface of the toner particles. Therefore, there was a problem that it was difficult to simultaneously improve environmental charging performance and suppress abrasiveness to the photoconductor drum.

[0005] The fine powder of strontium titanate containing silica has a more rounded shape than strontium titanate, and when added to toner particles, it has a higher effect of imparting fluidity than strontium titanate. Therefore, the fine powder of strontium titanate containing silica is easy to disperse, and disperses without being embedded in the soft toner particle surface of low-temperature fixing toner in a short mixing time. In addition, since it has a low tendency to aggregate on the toner particle surface, its abrasiveness to the photoconductor drum is somewhat weakened.

[0006] Regarding toners using fine powders of strontium titanate, Patent Document 1 discloses a toner using, as an external additive, fine powders of strontium titanate having on their surfaces Si-containing particles (sodium silicate) with a number-average equivalent circle diameter of 5 nm to 15 nm. The silica content in the fine powders of strontium titanate containing silica used in the present invention is less than 10% compared to the fine powders used in Patent Document 1, and the two fine powders are different as external additives. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2020-190724 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, even if fine powder of strontium titanate containing silica is used, the suppression of the abrasiveness to the photosensitive drum is insufficient, so it is desired to further suppress the abrasiveness by adding silica particles having a particle size larger than that of the fine powder as a spacer. However, since the fine powder of strontium titanate containing silica has high fluidity, the silica particles added as a spacer are washed away on the surface of the toner particles and fall into the depressions on the surface of the toner particles, which causes a problem that the spacer function is no longer fulfilled.

[0009] The present invention has been made based on the above circumstances, and its object is to provide a toner, a two-component developer, an image forming apparatus, and a method for producing a toner, which contain a fine powder of strontium titanate containing silica as an external additive and silica particles, and which can achieve both improved environmental charging performance and suppressed abrasiveness to a photosensitive drum. [Means for solving the problem]

[0010] In order to solve the above problems, the present invention provides the following toner, two-component developer, image forming apparatus, and method for producing toner.

[0011] The toner of the present invention, which has been made to solve the above problems, is a toner having an external additive attached to the surface of toner particles having a softening point of 110° C. or less, the toner particles containing a crystalline polyester resin and a wax. The external additive contains a fine powder in which the surface of a composition containing strontium titanate and silica has been hydrophobized with a silane compound, and silica particles. The number average equivalent circle diameter of primary particles of the fine powder is 20 nm or more and 50 nm or less, and the number average equivalent circle diameter of primary particles of the silica particles is 50 nm or more and 200 nm or less. In the following, the "fine powder in which the surface of a composition containing strontium titanate and silica has been hydrophobized with a silane compound" is also simply referred to as "fine powder".

[0012] The two-component developer of the present invention, which has been made to solve the above problems, is characterized by containing the toner of the present invention and a carrier.

[0013] The image forming apparatus of the present invention, which has been made to solve the above problems, is characterized by using the two-component developer of the present invention.

[0014] The toner manufacturing method of the present invention, which has been made to solve the above-mentioned problems, includes a first external addition step of mixing the fine powder with the toner particles to cause the fine powder to adhere to the surfaces of the toner particles, and a second external addition step of mixing the silica particles with the toner particles to cause the silica particles to adhere to the surfaces of the toner particles, and is characterized in that the second external addition step is performed after the first external addition step. Effect of the Invention

[0015] According to the present invention, it is possible to provide a toner, a two-component developer, an image forming apparatus, and a method for producing a toner, which contain strontium titanate fine powder and silica particles as external additives, and which can achieve both improved environmental charging performance and suppressed abrasiveness to a photosensitive drum. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a conceptual diagram showing a state where strontium titanate is attached to the toner particle surface of a non-low-temperature fixing toner in a short external addition time (top), and a state where silica particles are further externally added (bottom). [Diagram 2] FIG. 1 is a conceptual diagram showing a state where strontium titanate is attached to the toner particle surface of a non-low-temperature fixing toner for a long external addition time (top), and a state where silica particles are further externally added (bottom). [Diagram 3] FIG. 2 is a conceptual diagram showing a state in which strontium titanate is attached to the surface of a toner particle of a low-temperature fixing toner in a short external addition time. [Figure 4] FIG. 2 is a conceptual diagram showing a state in which strontium titanate is attached to the surface of a toner particle of a low-temperature fixing toner for a long external addition time. [Diagram 5] FIG. 1 is a conceptual diagram showing a state where fine powder is adhered to the surface of a toner particle of a low-temperature fixing toner in a short external addition time (top), and a state where silica particles are further externally added (bottom). [Figure 6] This is a conceptual diagram showing a state where fine powder is attached to the toner particle surface of a low-temperature fixing toner by a slightly long external addition time (top), and a state where silica particles are further attached by a short external addition time (bottom). [Figure 7] 1 is an image of the surface of the toner particles after external addition obtained in Example 11, taken with a scanning electron microscope (SEM). [Figure 8] 1 is an image of the surface of the toner particles after external addition obtained in Example 20, taken with a scanning electron microscope (SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention includes a toner, a two-component developer, an image forming apparatus, and a method for producing the toner, which will be described in detail below.

[0018] [toner] The toner according to the present invention is a toner having an external additive attached to the surface of the toner particles. If necessary, the toner may further contain an optional component within a range that does not impair the effects of the present invention. The volume average particle size of the primary particles of the toner particles is not particularly limited, but examples thereof include toner particles having a volume average particle size of 4 μm or more and 8 μm or less.

[0019] Examples of the binder resin in the toner according to the present invention include polyester resins, polystyrene resins such as styrene-acrylic resins, (meth)acrylic acid ester resins, polyolefin resins, polyurethane resins, and epoxy resins. Among these, one type may be used alone, or two or more types may be used in combination.

[0020] <Binding resin> The polyester resin used for the binder resin is usually obtained by polycondensation reaction of one or more selected from a dihydric alcohol component and a trihydric or higher polyhydric alcohol component with one or more selected from a divalent carboxylic acid and a trivalent or higher polycarboxylic acid by a known method via an esterification reaction or an ester exchange reaction.

[0021] The conditions for the polycondensation reaction may be appropriately set depending on the reactivity of the monomer components, and the reaction may be terminated when the polymer has suitable physical properties. For example, the reaction temperature is about 170 to 250° C., and the reaction pressure is about 5 mmHg to normal pressure.

[0022] Examples of the dihydric alcohol component include alkylene oxide adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane; Examples of the diols include glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; bisphenol A; propylene adducts of bisphenol A; ethylene adducts of bisphenol A; and hydrogenated bisphenol A.

[0023] Examples of trihydric or higher polyhydric alcohol components include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, sucrose (cane sugar), 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.

[0024] In the present invention, the above dihydric alcohol components and trihydric or higher polyhydric alcohol components may be used alone or in combination of two or more.

[0025] Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, cyclohexanedicarboxylic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, n-dodecylsuccinic acid, n-octylsuccinic acid, isooctenylsuccinic acid, isooctylsuccinic acid, and acid anhydrides and lower alkyl esters thereof.

[0026] Examples of trivalent or higher polyvalent carboxylic acids include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, and acid anhydrides and lower alkyl esters thereof.

[0027] In the present invention, among the above divalent carboxylic acids and trivalent or higher polyvalent carboxylic acids, one kind may be used alone, or two or more kinds may be used in combination.

[0028] The toner particles according to the present invention contain a crystalline polyester resin. That is, in the toner of the present invention, the binder resin preferably contains a crystalline polyester resin and an amorphous polyester resin. The crystalline polyester resin is dispersed in the amorphous polyester resin.

[0029] In the present invention, crystalline resins and amorphous resins are distinguished by their crystallinity index, with a resin having a crystallinity index in the range of 0.6 to 1.5 being crystalline resins, and a resin having a crystallinity index less than 0.6 or more than 1.5 being amorphous resins. Resins having a crystallinity index greater than 1.5 are amorphous, and resins having a crystallinity index less than 0.6 have low crystallinity and many amorphous portions.

[0030] The crystallinity index is a physical property that is an index of the degree of crystallization of a resin, and is defined by the ratio of the softening point to the highest endothermic peak temperature (softening point / highest endothermic peak temperature). Here, the highest endothermic peak temperature refers to the temperature of the highest endothermic peak observed. In a crystalline polyester resin, the highest peak temperature is the melting point, and in an amorphous polyester resin, the highest endothermic peak is the glass transition point.

[0031] The degree of crystallization can be controlled by adjusting the types and ratio of raw material monomers, as well as production conditions (for example, reaction temperature, reaction time, cooling rate), and the like.

[0032] As described in the "Background Art" and "Problems to be Solved by the Invention" columns of this specification, the present invention solves the problems associated with low-temperature fixing toners, and therefore the softening point of the toner particles according to the present invention is 110° C. or lower. The softening point is preferably 90° C. or higher and 110° C. or lower, more preferably 100° C. or higher and 110° C. or lower, and even more preferably 105° C. or higher and 110° C. or lower. If the softening point is below the lower limit, the fine powder is likely to be embedded in the surface of the toner particles, deteriorating dispersibility and also deteriorating dispersibility of the silica particles, which may increase the amount of film loss on the photoconductor drum and degrade environmental charging performance.

[0033] In order to set the softening point of the toner particles within the above range, the softening point of the crystalline polyester resin is preferably from 70° C. to 110° C. The softening point of the toner particles can be set within the above range by adjusting the content ratio of the crystalline polyester resin and the amorphous polyester resin in the toner particles.

[0034] (Crystalline polyester resin) The crystalline polyester resin is a polyester resin having a crystallinity index of 0.6 to 1.5, preferably a polyester resin having a crystallinity index of 0.8 to 1.2. The crystalline polyester resin is obtained, for example, by polycondensation of a polybasic acid and a polyhydric alcohol. For example, it can be produced by a known method such as that described in JP-A-2006-113473.

[0035] Examples of polyhydric alcohols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, neopentyl glycol, and 1,4-butenediol, but it is preferable to use a polyhydric alcohol that promotes the crystallinity of the resin, such as an aliphatic diol having 2 to 8 carbon atoms. These polyhydric alcohols may be used alone or in combination of two or more.

[0036] From the viewpoint of enhancing the crystallinity of the resin, the content of the aliphatic diol having 2 to 8 carbon atoms in the polyhydric alcohol is preferably 80 mol % or more, and when two or more kinds of aliphatic diols having 2 to 8 carbon atoms are used, the content of one kind of aliphatic diol having 2 to 8 carbon atoms in the polyhydric alcohol is desirably 70 mol % or more.

[0037] Examples of polybasic acids include aliphatic dicarboxylic acids having 2 to 30 carbon atoms, preferably 2 to 8 carbon atoms, such as fumaric acid, adipic acid, oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, sebacic acid, azelaic acid, n-dodecyl succinic acid, and n-dodecenyl succinic acid; aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid; alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid; and polyvalent carboxylic acids having three or more valences, such as trimellitic acid and pyromellitic acid. In order to obtain a high degree of crystallinity (crystallinity index), aliphatic dicarboxylic acids are preferred, and aliphatic dicarboxylic acids having 2 to 8 carbon atoms are more preferred. These polybasic acids may be used alone or in combination of two or more kinds.

[0038] The acid value of the crystalline polyester resin is preferably 5 mgKOH / g or more and 20 mgKOH / g or less, and the hydroxyl value of the crystalline polyester resin is preferably 5 mgKOH / g or more and 20 mgKOH / g or less.

[0039] The molecular weight of the crystalline polyester resin is preferably such that the weight average molecular weight (Mw) is from 5,000 to 100,000, and the number average molecular weight (Mn) is from 3,000 to 20,000. In the present invention, the weight average molecular weight and the number average molecular weight are values ​​measured by gel permeation chromatography (GPC), in which chloroform is used as the mobile phase and polystyrene is used as the standard substance.

[0040] (Amorphous polyester resin) The amorphous polyester resin is a polyester resin having a crystallinity index of less than 0.6 or more than 1.5, and preferably a polyester resin having a crystallinity index of more than 1.5. The amorphous polyester resin is obtained, for example, by polycondensation of a polybasic acid and a polyhydric alcohol.

[0041] As the polybasic acid, known monomers for polyester synthesis can be used, and examples thereof include aromatic carboxylic acids such as terephthalic acid, isophthalic acid, phthalic anhydride, trimellitic acid, trimellitic anhydride, pyromellitic acid, and naphthalenedicarboxylic acid, aliphatic carboxylic acids such as maleic anhydride, fumaric acid, succinic acid, alkenyl succinic anhydride, and adipic acid, and methyl esters of these polybasic acids, etc. These polybasic acids may be used alone or in combination of two or more.

[0042] As the polyhydric alcohol, known monomers for polyester synthesis can be used, and examples thereof include aliphatic polyhydric alcohols such as ethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, and glycerin, alicyclic polyhydric alcohols such as cyclohexanediol, cyclohexanedimethanol, and hydrogenated bisphenol A, and aromatic diols such as an ethylene oxide adduct of bisphenol A and a propylene oxide adduct of bisphenol A. These polyhydric alcohols may be used alone or in combination of two or more.

[0043] The polycondensation reaction of the polybasic acid and the polyhydric alcohol can be carried out according to a conventional method, for example, by contacting the polybasic acid with the polyhydric alcohol in the presence or absence of an organic solvent and in the presence of a polycondensation catalyst (such as tin octylate), and the reaction is terminated when the acid value and softening point of the polyester produced reach the desired value. This results in an amorphous polyester resin. If a methyl ester of the polybasic acid is used as a part of the polybasic acid, a demethanol polycondensation reaction is carried out. In this polycondensation reaction, for example, the carboxyl group content at the end of the polyester can be adjusted by appropriately changing the blending ratio and reaction rate of the polybasic acid and the polyhydric alcohol, and thus the properties of the obtained amorphous polyester resin can be modified. In addition, if trimellitic anhydride is used as the polybasic acid, a carboxyl group can be easily introduced into the main chain of the polyester.

[0044] The polycondensation reaction between the polybasic acid and the polyhydric alcohol is usually carried out at a temperature of about 150° C. to 300° C., preferably about 170° C. to 280° C. The polycondensation reaction can be carried out under normal pressure, reduced pressure or increased pressure, and it is desirable to appropriately adjust the pressure in the system while monitoring the progress of the polycondensation reaction by monitoring physical property values ​​(e.g., acid value, melting point, etc.) and the stirring torque or power value of the reactor.

[0045] The acid value of the amorphous polyester resin is preferably from 10 KOHmg / g to 30 KOHmg / g, and more preferably from 15 KOHmg / g to 25 KOHmg / g.

[0046] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 50,000 or less, and the number average molecular weight (Mn) is preferably 1,000 or more and 10,000 or less. In the present invention, the weight average molecular weight and the number average molecular weight are values ​​measured by gel permeation chromatography (GPC), in which tetrahydrofuran (THF) is used as the mobile phase and polystyrene is used as the standard substance.

[0047] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 55°C or higher and 70°C or lower.

[0048] <Wax> The toner particles according to the present invention contain a wax as a release agent. The wax may be a wax used in the field of electrophotography. For example, synthetic ester wax, paraffin wax, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, polypropylene wax, carnauba wax, etc. may be used. One of these may be used alone, or two or more may be used in combination. The content of the wax in the toner particles is not particularly limited, but is preferably 0.5 to 10% by mass.

[0049] <Other internal additives> Furthermore, the toner particles according to the present invention may contain colorants, charge control agents, etc. Components other than the external additives are collectively called internal additives. As colorants, organic dyes, organic pigments, inorganic dyes, inorganic pigments, etc. used in the field of electrophotography can be used. As charge control agents, charge control agents for positive charge control and negative charge control used in the field of electrophotography can be used.

[0050] <External additives> In the present invention, the external additive contains a fine powder of a composition containing strontium titanate and silica, the surface of which is hydrophobized with a silane compound, and silica particles. The fine powder has a number average equivalent circle diameter of primary particles of 20 nm to 50 nm, and the silica particles have a number average equivalent circle diameter of primary particles of 50 nm to 200 nm. This allows the toner of the present invention to achieve both improved environmental charging performance and suppressed abrasiveness to the photoconductor drum.

[0051] The fine powder of a composition containing strontium titanate and silica, the surface of which is hydrophobized with a silane compound, can be produced, for example, by the following procedures (1) to (5).

[0052] (1) Metatitanic acid obtained by the sulfuric acid method is deironized and bleached, then desulfurized by adding an aqueous solution of sodium hydroxide, and then neutralized with hydrochloric acid. After filtration and washing with water, a washed cake is obtained. (2) Water is added to the washed cake to make a slurry, and then hydrochloric acid is added to perform a peptization process. This is solution 1, and is mixed with solution 2, an aqueous solution of strontium chloride, and solution 3, an aqueous solution of sodium silicate. The mixing ratio of solutions 1, 2, and 3 is set so that the molar ratio of (Sr+Si) / Ti is 1.2. (3) Heat the mixed solution to 90°C under a nitrogen gas atmosphere, add an aqueous sodium hydroxide solution and stir for 2 hours to complete the reaction. (4) After the reaction, the slurry is cooled to 50°C, hydrochloric acid is added, and the mixture is stirred for 2 hours. The resulting precipitate is washed, separated by filtration, and then dried. (5) The dried product is ground in a blender for 1 minute, and the coarse powder is removed using a sieve with a mesh size of 32 μm. The resulting fine powder substrate is then surface-coated with a silane coupling agent. Examples of methods for surface-coating with a silane coupling agent include surface treatments commonly used in the art using hexamethyldisilazane (HMDS), dimethyl-dichlorosilane (DDS), octylsilane (OTAS), polydimethylsiloxane (PDMS), etc.

[0053] In the toner of the present invention, the molar ratio Si / Ti of silicon (Si) to titanium (Ti) in the fine powder in which the surface of the composition containing strontium titanate and silica is hydrophobized with a silane compound is preferably 0.03 or more and less than 1.0. If Si / Ti is less than the above lower limit, the negative charging property of the fine powder is weak, so that when the toner to which the fine powder is added is left in a high humidity environment, the charging rate decreases quickly and the fog value increases (environmental charging performance deteriorates). If Si / Ti is more than the above upper limit, the negative charging property of silica is strongly expressed, so that when the toner to which the fine powder is added is continuously printed in a low humidity environment, the toner becomes excessively charged, the mixing with the toner supplied from the cartridge deteriorates, and the toner scatters, so that the fog value increases (environmental charging performance deteriorates).

[0054] The silica particles as an external additive in the present invention are not particularly limited as long as they satisfy the number average equivalent circle diameter of the primary particles. Examples of the silica particles include those manufactured by Cabot Corporation under the product name "TG-C191 (number average equivalent circle diameter 115 nm)", those manufactured by Shin-Etsu Chemical Co., Ltd. under the product names "X-24-9163A (number average equivalent circle diameter 110 nm)" and "X-24-9404 (number average equivalent circle diameter 50 nm)", and those manufactured by Teika Corporation under the product name "MSN-005L (number average equivalent circle diameter 80 nm)".

[0055] The fine powder in the toner of the present invention has a number average equivalent circle diameter of primary particles of preferably 25 nm or more, more preferably 30 nm or more. Also, it is preferably 45 nm or less, more preferably 40 nm or less. If the number average equivalent circle diameter of primary particles of the fine powder is less than the lower limit, the dispersibility of the silica particles may deteriorate and the amount of film loss on the photoconductor drum may increase. If the number average equivalent circle diameter of primary particles of the fine powder exceeds the upper limit, the dispersibility of both the fine powder and the silica particles may deteriorate, the amount of film loss on the photoconductor drum may increase, and the environmental charging performance may deteriorate.

[0056] The silica particles in the toner of the present invention preferably have a number average equivalent circle diameter of primary particles of 75 nm to 150 nm. If the number average equivalent circle diameter of primary particles of the silica particles is outside the above range, the dispersibility of the silica particles may deteriorate, and the amount of film loss on the photoconductor drum may increase.

[0057] The fine powder in the toner of the present invention preferably has an adhesion strength to the surface of the toner particles of 70% or more and 95% or less, more preferably 80% or more and 95% or less, and even more preferably 85% or more and 95% or less. If the adhesion strength is less than the lower limit, the dispersibility of the fine powder and the silica particles may deteriorate, the amount of film loss on the photoconductor drum may increase, and the environmental charging performance may deteriorate. If the adhesion strength exceeds the upper limit, the fine powder is excessively embedded in the surface of the toner particles, and the dispersibility may deteriorate slightly, and the dispersibility of the silica particles may deteriorate slightly, and the amount of film loss on the photoconductor drum may increase, and the environmental charging performance may deteriorate.

[0058] The silica particles in the toner of the present invention preferably have an adhesion strength to the surface of the toner particles of 40% or more and 70% or less, more preferably 50% or more and 70% or less. If the adhesion strength is less than the lower limit, the dispersibility of the silica particles may deteriorate, and the amount of film loss on the photosensitive drum may increase. If the adhesion strength exceeds the upper limit, the dispersibility of the silica particles may also deteriorate, and the amount of film loss on the photosensitive drum may increase.

[0059] In the toner of the present invention, the fluidity imparting efficiency of the fine powder to the toner particles is preferably 0.04 or more. The fine powder, in which the surface of the composition containing strontium titanate and silica is hydrophobized with a silane compound, can be produced by performing a surface treatment with a silane coupling agent as described below, and the fluidity imparting efficiency can be changed by changing the silane coupling agent used for the surface treatment. In addition, the fluidity imparting efficiency differs depending on the number-average circle equivalent diameter of the primary particles of the fine powder. If the fluidity imparting efficiency is less than the above lower limit, the dispersibility of the fine powder and the dispersibility of the silica particles are also deteriorated, which may increase the amount of film loss on the photoconductor drum and may deteriorate the environmental charging performance.

[0060] The silica particles in the toner of the present invention preferably have a circularity of 0.95 or more. If the circularity is less than the lower limit, the dispersibility of the silica particles may deteriorate, and the amount of film loss on the photosensitive drum may increase.

[0061] The fine powder in the toner of the present invention preferably has a dispersion index of -10 or more, more preferably -9 or more. If the dispersion index falls below the lower limit by shortening the external addition time of the fine powder, the dispersibility of the silica particles also deteriorates, and there is a risk of an increase in the amount of film loss on the photoreceptor drum and a deterioration in environmental charging performance.

[0062] The silica particles in the toner of the present invention preferably have a dispersion index of not more than 25, more preferably not more than 20. If the dispersion index exceeds the upper limit as a result of extending the external addition time of the silica particles, the dispersion of the silica particles may deteriorate, and the amount of film loss on the photoconductor drum may increase.

[0063] The content of the fine powder in the toner of the present invention is preferably 0.1 parts by mass or more and 5.0 parts by mass or less per 100 parts by mass of the toner particles. The content of the silica particles in the toner of the present invention is preferably 0.5 parts by mass or more and 4.0 parts by mass or less per 100 parts by mass of the toner particles.

[0064] [Toner manufacturing method] The toner manufacturing method according to the present invention includes a kneading step S1 in which a kneaded mixture is produced by kneading toner raw materials including a binder resin, a wax, and a colorant, a crushing step S2 in which the kneaded mixture produced in the kneading step S1 is crushed to produce toner particles, a classification step S3 in which the toner particles produced in the crushing step S2 are classified, and an external addition step S4 in which an external additive is added to the toner particles after classification in the classification step S3.

[0065] (Kneading process S1) In the kneading step S1, the binder resin, wax, colorant, and charge control agent, which are the raw materials of the toner particles, are mixed in a mixer such as a Henschel mixer, and then kneaded using a kneader to obtain a kneaded product. The kneading is performed by heating to a temperature equal to or higher than the softening point of the binder resin and lower than its thermal decomposition temperature. This melts or softens the binder resin, and allows the colorant, wax, charge control agent, and the like to be dispersed in the binder resin. The specific heating temperature during kneading is preferably, for example, 80°C to 200°C, and more preferably 100°C to 150°C. The kneader may be a kneader, a twin-screw extruder, a two-roll mill, a three-roll mill, or a lab blast mill. Examples of such kneaders include single- or twin-screw extruders such as TEM-100B (trade name, manufactured by Toshiba Machine Co., Ltd.), PCM-65, PCM-65 / 87, and PCM-30 (all of which are trade names, manufactured by Ikegai Corporation), and open-roll type kneaders such as Kneadex (trade name, manufactured by Mitsui Mining Co., Ltd.). The kneading step may be performed using a plurality of kneaders.

[0066] (Crushing process S2) In the pulverization step S2, the kneaded product obtained in the kneading step S1 is solidified by cooling or the like, and the solidified product is roughly crushed to obtain a roughly crushed product. As a pulverizer for roughly crushing, for example, a speed mill, a hammer mill, or a cutter mill can be used. After that, the roughly crushed product is finely crushed (fine-pulverization step). In the fine-pulverization step, for example, a jet-type pulverizer that uses a supersonic jet stream to pulverize the product, or an impact-type pulverizer that introduces the above-mentioned roughly crushed product into a space formed between a rotor and a stator (liner) rotating at high speed can be used. Note that the finely crushed particle group obtained in the pulverization step S2 may be collected as toner particles without performing the following classification step S3.

[0067] (Classification process S3) In the classification step S3, the finely pulverized particles obtained in the pulverization step S2 are classified using a classifier to obtain fine particles having a volume average particle size of 4 μm to 8 μm. As the classifier, for example, a rotary wind classifier (rotary wind classifier) ​​can be used.

[0068] (External addition process S4) In the external addition process S4, the fine particles (toner particles) obtained in the classification process S3 are mixed with an external additive using a mixer, and the external additive is attached to the surface of each fine particle to obtain a toner particle group, which is then recovered as toner (external additive toner).

[0069] The external addition process S4 includes a first external addition process in which the fine powder is mixed with the toner particles to cause the fine powder to adhere to the surfaces of the toner particles, and a second external addition process in which the silica particles are mixed with the toner particles to cause the silica particles to adhere to the surfaces of the toner particles.

[0070] In the toner production method of the present invention, it is preferable to carry out the second external addition step after carrying out the first external addition step.

[0071] The fine powder is sufficiently dispersed in a short external addition time, and exists on the surface of the toner particles with few aggregates. From that state, it is mixed for a slightly longer time to create a state in which the fine powder is embedded to the extent that it does not impair the environmental charging performance, as shown in the upper part of Figure 6. This state can suppress the silica particles added later from being washed away on the surface of the toner particles, and in turn, as shown in the lower part of Figure 6, can suppress the silica particles from falling into the concaves of the unevenness present on the surface of the pulverized toner particles (particles that have been through the pulverization step S2). Therefore, the silica particles can be made to act as spacers, and the abrasiveness to the photoconductor drum can be suppressed. If such a state is not created, as shown in Figure 5, the silica particles will be washed away due to the high fluidity of the fine powder, and the silica particles will fall into the concaves of the unevenness present on the surface of the pulverized toner particles, and the silica particles may not be able to contribute to suppressing the abrasiveness to the photoconductor drum.

[0072] In the toner manufacturing method of the present invention, when the mixing rotation speed in the first external addition step is D and the mixing rotation speed in the second external addition step is E, it is preferable that D / E is equal to or greater than 1. If D / E is less than 1, the dispersibility of the silica particles is deteriorated, and the amount of film loss on the photoconductor drum may increase.

[0073] [Two-component developer] The two-component developer according to the present invention includes the toner according to the present invention and a carrier. The two-component developer can be produced by mixing the toner and the carrier using a known mixer. The weight ratio of the toner to the carrier is not particularly limited, and may be, for example, 3:97 to 12:88.

[0074] The carrier is stirred and mixed with the toner in the developing tank, giving the toner a desired charge. The carrier also acts as an electrode between the developing device and the photoconductor, carrying the charged toner to the electrostatic latent image on the photoconductor to form a toner image. The carrier is held on the developing roller of the developing device by magnetic force, and after acting in development, it returns to the developing tank, where it is stirred and mixed with new toner again and is used repeatedly until the end of its life.

[0075] The carrier has a carrier core material and a resin coating layer that coats the carrier core material. The carrier core material is not particularly limited as long as it is used in the electrophotographic field. Specific examples of the material of the carrier core material include magnetic metals such as iron, copper, nickel, and cobalt, and magnetic metal oxides such as ferrite and magnetite. The volume average particle size of the carrier core material is not particularly limited, and may be, for example, 30 μm or more and 100 μm or less. The resin coating layer preferably contains a silicone resin or an acrylic resin. Silicone resin can delay the progression of contamination of the carrier coat layer, and is suitable for long-life use. EXAMPLES

[0076] The present invention will be described below based on examples and comparative examples, but the present invention is not limited to these examples. First, measurements in the examples will be described.

[0077] <Method of measuring the softening point of toner particles> Using a flow characteristic evaluation device (product name: Flow Tester CFT-100C, manufactured by Shimadzu Corporation), 1 g of sample was heated at a temperature increase rate of 6°C per minute and subjected to a load of 20 kgf / cm 2 The softening temperature was determined as the temperature at which the sample started to flow out of the die (nozzle diameter 1 mm, length 1 mm) under a pressure of (9.8 × 105 Pa).

[0078] <Method for measuring adhesive strength of external additives> The adhesion strength of each external additive to the toner particles (toner base particles) was measured by the following procedure. (1) 2.0 g of toner is added to 40 ml of a 0.2% by mass aqueous solution of Triton (polyoxyethylene octylphenyl ether), and the mixture is stirred for 1 minute. (2) The above aqueous solution is irradiated with ultrasonic waves using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., model: US-300T) (output: 40 μA, 4 minutes). (3) The aqueous solution after the ultrasonic irradiation is left to stand for 3 hours, and the toner and the liberated external additives are separated. (4) After removing the supernatant, add approximately 50 ml of pure water to the precipitate and stir for 5 minutes. (5) The mixture is subjected to suction filtration using a membrane filter having a pore size of 1 μm (manufactured by Advantec Co., Ltd.). (6) The toner remaining on the filter is vacuum dried overnight. (7) Using an X-ray fluorescence analyzer (Rigaku Corporation, model: ZSX Primus II), the intensities of the elements (Si) and (Ti) in the external additive of 1 g of toner before and after the series of processes (1) to (6) above are analyzed, and the adhesion strength of the external additive is calculated using the following formula.

[0079] Adhesion strength of silica particles (%) = {(Si strength after treatment) / (Si strength before treatment)} x 100 Adhesion strength (%) of fine powder of a composition containing strontium titanate and silica, the surface of which has been hydrophobized with a silane compound = {(Ti strength after treatment) / (Ti strength before treatment)} x 100

[0080] <Method of measuring toner fluidity> The weight of 30 ml of toner was measured in 180 seconds using a bulk density measuring device (manufactured by Ito Seisakusho Co., Ltd., JIS-K-5101), and the bulk density was taken as the flowability value.

[0081] <Calculation method for efficiency of imparting fluidity to toner particles by fine powder> Four toners with different amounts of fine powder added per 100 parts by mass of toner particles (addition amounts of 0.3 parts by mass, 0.6 parts by mass, 0.9 parts by mass, and 1.2 parts by mass) were prepared. Specifically, each was mixed for 120 seconds at a rotation speed of 3500 rpm using an FM mixer (manufactured by Nippon Coke & Engineering Co., Ltd., product name: FM-20) to obtain toners with external additives. The fluidity of each toner with external additives was measured and then graphed, and an approximate straight line was drawn to calculate the increase in fluidity per 0.1 part by mass of fine powder as the fluidity imparting efficiency.

[0082] <Method for measuring circularity of silica particles> 20 silica particles were photographed using a scanning electron microscope (Hitachi High-Technologies Corporation, product name: S-4800), and the area S and perimeter L were measured from the obtained images. The circularity was calculated as 4πS / L. 2 asked for.

[0083] <Method of measuring toner resistance> 1 g of toner was placed in a φ25 mm container and compressed for 20 seconds at a force of 20 MPa to obtain a solid sample with a diameter of 25 mm and a thickness of 2 mm. The resistance of the toner was measured using a 2550A capacitance bridge (manufactured by Andeen-Hagerling).

[0084] <Calculation method for dispersion index of fine powder> The dispersion index B of the fine powder was calculated by the following formula (1). B = (XY) / (xy) (1) (In formula (1), X is the resistance value (GΩ) of the toner when x parts by mass of fine powder is added to 100 parts by mass of toner particles. Y is the resistance value (GΩ) of the toner when y parts by mass of fine powder is added to 100 parts by mass of toner particles.)

[0085] <Calculation method of dispersion index of silica particles> The dispersion index C of the silica particles was calculated using a powder property evaluation device (manufactured by Hosokawa Micron Corporation, product name: Powder Tester PT-X) according to the following procedure. (1) Add 20g of toner to a 50ml Eye Boy and leave it for two weeks. (2) 5 g of the toner that has been compacted under its own weight is sieved as the toner to be evaluated, and the weight of the residue is measured. Three types of sieves with openings of 250 μm, 150 μm, and 75 μm are used, and the toner to be evaluated is placed on three sieves stacked from the top in order of the largest opening, and the sieves are vibrated with an amplitude of 0.5 mm for 5 seconds. (3) The dispersion index C of the silica particles is calculated by the following formula (2). C=(weight of residue on 250 μm mesh+weight of residue on 150 μm mesh×0.6+weight of residue on 75 μm mesh×0.2) / weight of toner to be evaluated

[0086] <How to output printed materials> A color multifunction printer (model: BP-20C25, manufactured by Sharp Corporation) was used as the evaluation machine. The evaluation machine was operated in an environmental testing room under three different environments: temperature 25°C, humidity 5% RH, temperature 25°C, humidity 50% RH, and temperature 25°C, humidity 80% RH, and 90,000 sheets of an image were printed in which 10% of the printable area of ​​A4 paper was filled with cyan toner.

[0087] <Method for evaluating the environmental charging performance of toner> As described above, an image was printed using the evaluation machine in which 10% of the printable area of ​​A4 paper was filled with cyan toner, and the brightness of a specific area of ​​the image that was not filled was measured using a color difference meter (manufactured by Nippon Denshoku Industries Co., Ltd., model: ZE6000). The difference between this brightness and the brightness measured before printing was taken as the overcast value.

[0088] Based on the measured fog values, the environmental charging performance of the toner was evaluated according to the following criteria: The specified fog value is a specified value determined by the evaluation machine and the evaluation content. ◎ (Excellent): The measured value is 80% or less of the specified fogging value. ◯ (Good): The measured value is more than 80% and 90% or less of the specified fogging value. △ (Fair): The measured value is more than 90% and 100% or less of the specified fogging value. × (Fail): The measured value is more than 100% of the specified fogging value.

[0089] <Method for evaluating the amount of film loss on photoconductor drum> For the photoconductor drums of the examples and comparative examples, the difference between the photoconductor film thickness before and after printing 90,000 sheets (change in photoconductor film thickness due to printing 90,000 sheets) was measured using an eddy current film thickness meter (manufactured by Fisher), and the measured value was converted into the film thickness loss per 100,000 rotations of the photoconductor drum. Based on this film thickness loss per 100,000 rotations, evaluation was made according to the following criteria.

[0090] ◎ (Excellent): The amount of film loss is less than 0.8 μm. ◯ (Good): The amount of film loss is 0.8 μm or more and less than 1.0 μm. △ (Fair): The amount of film loss is 1.0 μm or more and less than 2.0 μm. × (Fail): The amount of film loss is 2.0 μm or more.

[0091] <Toner overall evaluation method> Based on the above evaluation results (evaluation of the environmental charging performance of the toner and evaluation of the amount of film loss on the photosensitive drum), a comprehensive evaluation was made according to the following criteria.

[0092] ◎(Excellent): All evaluation items are ◎. ○ (Good): The lowest rating of the two items is ○. △(Acceptable): The lowest rating of the two items is △. × (Fail): The lowest rating of the two items is ×.

[0093] Next, the steps of producing the toner and two-component developer in Examples 1 to 20 and Comparative Examples 1 to 7 will be described.

[0094] <Preparation of toner particles> In Examples 1 to 15, 18 to 20 and Comparative Examples 3 to 7, toner particles were prepared as follows.

[0095] The following materials were premixed for 5 minutes using an airflow mixer (Henschel mixer, manufactured by Mitsui Mining Co., Ltd. (now Nippon Coke and Engineering Co., Ltd.), model: FM20C) [mixing process]. Binder resin: Amorphous polyester resin 67% by weight Crystalline polyester resin 20% by mass Colorant: CI Pigment Blue 15:3 (DIC Corporation) 7% by weight Release agent: Monoester wax (NOF Corporation, product name: WEP-3) 5% by mass Charge control agent: Salicylic acid compound (Orient Chemical Industry Co., Ltd., product name: Bontron E-84) 1% by mass

[0096] Next, the mixture was melt-kneaded using an open roll type continuous kneader (manufactured by Mitsui Mining Co., Ltd. (currently Nippon Coke and Engineering Co., Ltd.), model: MOS320-1800) to obtain a melt-kneaded product [kneading step].

[0097] The open roll conditions were as follows: heating roll supply side temperature 130° C., discharge side temperature 100° C., cooling roll supply side temperature 40° C., discharge side temperature 25° C. The heating roll and cooling roll had a diameter of 320 mm and an effective length of 1550 mm, and the gap between the rolls on both the supply side and discharge side was 0.3 mm. The rotation speed of the heating roll was 75 rpm, the rotation speed of the cooling roll was 65 rpm, and the supply amount of the toner raw material was 5.0 kg / h.

[0098] The resulting molten mixture was cooled with a cooling belt, and then coarsely pulverized using a speed mill with a φ2 mm screen to obtain a coarsely pulverized product. The coarsely pulverized product was finely pulverized using a jet pulverizer (manufactured by Nippon Pneumatic Mfg. Co., Ltd., model: IDS-2) to obtain a finely pulverized product [fine pulverization process].

[0099] Next, the resulting finely pulverized material was classified using an elbow jet classifier (manufactured by Nittetsu Mining Co., Ltd., model: EJ-LABO) to obtain toner particles [classification step].

[0100] In the above mixing process, the blending ratios were changed to 65% by mass of amorphous polyester resin and 22% by mass of crystalline polyester resin in Example 16, 63% by mass of amorphous polyester resin and 24% by mass of crystalline polyester resin in Example 17, and 87% by mass of amorphous polyester resin and 0% by mass of crystalline polyester resin in Comparative Examples 1 and 2, thereby obtaining toner particles with different softening points.

[0101] <Preparation of fine powder> Metatitanic acid obtained by the sulfuric acid method was bleached to remove iron, and then desulfurized by adding an aqueous sodium hydroxide solution. It was then neutralized with hydrochloric acid, filtered, and washed to obtain a washed cake. Water was added to the washed cake to make a slurry, and hydrochloric acid was added to perform a peptization treatment. This was made into solution 1, and solution 2, an aqueous strontium chloride solution, and solution 3, an aqueous sodium silicate solution, were mixed. The mixing ratio of solutions 1, 2, and 3 was set so that the molar ratio of (Sr+Si) / Ti was 1.2. The mixed solution was heated to 90°C under a nitrogen gas atmosphere, and the reaction was completed by stirring for 2 hours while adding an aqueous sodium hydroxide solution. The slurry after the reaction was cooled to 50°C, hydrochloric acid was added, and the mixture was stirred for 2 hours. The precipitate obtained after stirring was washed, separated by filtration, and then dried. The dried product was pulverized in a blender for 1 minute, and the fine powder base obtained after removing coarse powder with a sieve with an opening of 32 μm was surface-coated with a silane coupling agent. In Example 15, fine powder surface-treated with polydimethylsiloxane was used, while in other Examples and Comparative Examples, fine powder surface-treated with octylsilane was used. Due to this surface treatment, the fluidity imparting efficiency of the toner in Example 15 is lower than that of the other Examples, as shown in Table 1 below. The difference in fluidity imparting efficiency between Examples 1 to 4 and Comparative Examples 6 to 7 is due to the difference in the number average equivalent circle diameter of the primary particles of the fine powder.

[0102] <External Addition Process (Addition of External Additives to Toner Particles)> The external additive was added to the toner particles in a first external addition step and a second external addition step, and the external additive was adhered to the surface of the toner particles. In Example 11, the external additive was adhered to the surface of the toner particles under the following conditions.

[0103] In the first external addition step, 100 parts by mass of toner particles and 1.2 parts by mass of fine powder were placed in a container, and the contents of the container were mixed at a rotation speed of 3500 rpm for 180 seconds using an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd., product name: FM-20).

[0104] Next, in the second external addition step, 2.0 parts by mass of silica particles (manufactured by Cabot Corporation, product name: TG-C191) were added to the container and mixed for 120 seconds at a rotation speed of 2500 rpm using an FM mixer to obtain a mixture. This mixture was sieved using a 270 mesh sieve to obtain an externally added toner.

[0105] In Examples 1 to 10, 12 to 20 and Comparative Examples 1 to 7, the mixing time in the first external addition step (first external addition time) and the mixing time in the second external addition step (second external addition time) are changed to adjust the adhesion strength of the fine powder and silica particles to the toner particle surface. The external addition time is adjusted to achieve a target adhesion strength based on the results of a preliminary experiment, and the adhesion strength increases when the external addition time is extended. Note that, in Examples 14 to 18, the fluidity imparting efficiency of the fine powder, the softening point of the toner particles, and the circularity of the silica particles are changed under the same external addition time conditions.

[0106] <Preparation of carrier> A resin liquid was prepared by adding 10 parts by mass of PTFE (manufactured by Daikin Industries, Ltd., product name: LDE-410) as fluororesin microparticles to 100 parts by mass of silicone resin, and a carrier core material was immersed in this resin liquid to obtain carrier "SC-1."

[0107] <Preparation of two-component developer> The obtained toner with external additives and carrier "SC-1" were mixed for 20 minutes in a V-type mixer (manufactured by Tokuju Machinery Co., Ltd., product name: V-5) so that the toner concentration was 7% by mass, to prepare a two-component developer.

[0108] The evaluation results of the toners and two-component developers of Examples 1 to 20 and Comparative Examples 1 to 7 thus prepared are shown in Table 1 below.

[0109] [Table 1]

[0110] As is clear from Table 1, the toner and two-component developer of Examples 1 to 20, in which the softening point of the toner particles is 110°C or lower, the toner particles contain a crystalline polyester resin and a wax, and the surface of a composition containing strontium titanate and silica as an external additive is hydrophobized with a silane compound, contain a fine powder and silica particles, and the number average equivalent circle diameter of the primary particles of the fine powder is 20 nm or more and 50 nm or less, and the number average equivalent circle diameter of the primary particles of the silica particles is 50 nm or more and 200 nm or less, were excellent in both the evaluation of environmental charging performance and the evaluation of the amount of film loss on the photosensitive drum.

[0111] In contrast, Comparative Examples 3 to 7, which do not satisfy these requirements, were inferior to the Examples in at least one of the evaluation of environmental charging performance and the evaluation of the amount of film loss on the photoconductor drum. Note that Comparative Examples 1 and 2 have toner particles with a softening point of 115° C., which does not meet the condition that the toner particles have a softening point of 110° C. or less.

[0112] Focusing on Examples 5 to 8, which have different adhesion strengths of fine powder, it can be seen that Examples 6 and 7, in which the adhesion strength of fine powder is 70% or more and 95% or less, are superior in the evaluation of environmental charging performance and the evaluation of the amount of film loss on the photosensitive drum, compared to Examples 5 and 8, in which the adhesion strength of fine powder is outside that range.

[0113] Focusing on Examples 9 to 13, which have different adhesion strengths of silica particles, it can be seen that Examples 10 to 12, in which the adhesion strength of silica particles is 40% or more and 70% or less, are superior in the evaluation of environmental charging performance and the evaluation of the amount of film loss on the photosensitive drum, compared to Examples 9 and 13, in which the adhesion strength of silica particles is outside that range.

[0114] As described above, in Examples 14 to 18, the fluidity imparting efficiency of the fine powder, the softening point of the toner particles, and the circularity of the silica particles were changed under the same external addition time conditions.

[0115] Although Example 14 and Example 15 have the same number average equivalent circle diameter and adhesive strength of the primary particles of the fine powder and silica particles, as described above, Example 15 has a different surface treatment of the fine powder from the other Examples, and therefore the fluidity imparting efficiency by the fine powder is less than 0.40. It can be seen that Example 14, in which the fluidity imparting efficiency by the fine powder is 0.40 or more, is superior to Example 15 in the evaluation of environmental charging performance and the evaluation of the amount of film loss on the photoconductor drum.

[0116] Focusing on Examples 16 and 17, it can be seen that Example 16, which has a softening point of 105°C, and Example 17, which has a softening point of 100°C, also have excellent environmental charging performance evaluations and evaluations of the amount of film loss on the photosensitive drum, compared to Comparative Examples 3 to 7.

[0117] When comparing Example 18, in which the circularity of the silica particles is 0.936, with the other Examples, it can be seen that Example 14, in which the circularity of the silica particles is 0.980, etc. are superior in the evaluation of environmental charging performance and the evaluation of the amount of film loss on the photosensitive drum.

[0118] In Example 19, the external addition time of the fine powder was shortened and the dispersion index of the fine powder was reduced. It can be seen that Example 14 and the like, in which the dispersion index of the fine powder is -10 or more, are superior to Example 19 in the evaluation of environmental charging performance and the evaluation of the amount of film loss on the photoconductor drum.

[0119] In Example 20, the external addition time of silica particles was extended to increase the dispersion index of the silica particles. It can be seen that Example 14 and the like, in which the dispersion index of the silica particles is 25 or less, are superior to Example 20 in the evaluation of environmental charging performance and the evaluation of the amount of film loss on the photoconductor drum.

[0120] Furthermore, the SEM images shown in Figures 7 and 8 reveal that, compared to the externally-added toner of Example 20 (Figure 8), the silica particles in the externally-added toner of Example 11 (Figure 7) are not localized in the depressions on the toner particle surface, but are dispersed on the toner particle surface.

[0121] <Other embodiments> It should be noted that the embodiments disclosed herein are illustrative in all respects and are not intended to be limiting. Therefore, the technical scope of the present invention is not interpreted solely by the above-described embodiments, but is defined by the claims. The technical scope of the present invention includes all modifications within the scope and meaning equivalent to the claims. [Explanation of symbols]

[0122] 1. Fine powder of a composition containing strontium titanate and silica, the surface of which is hydrophobized with a silane compound 2. Strontium titanate 3. Silica particles

Claims

1. A toner having an external additive attached to the surface of a toner particle having a softening point of 110° C. or less, the toner particles comprise a crystalline polyester resin and a wax; the external additive contains a fine powder of a composition containing strontium titanate and silica, the surface of which is hydrophobized with a silane compound, and silica particles; The number average equivalent circle diameter of primary particles of the fine powder is 20 nm or more and 50 nm or less, The number average equivalent circle diameter of primary particles of the silica particles is 50 nm or more and 200 nm or less, the adhesion strength of the fine powder to the surface of the toner particle is 80% or more and 95% or less; The toner, wherein the adhesion strength of the silica particles to the surfaces of the toner particles is 40% or more and 64% or less.

2. 2. The toner according to claim 1, The toner, wherein the efficiency of imparting fluidity to the toner particles by the fine powder is 0.04 or more.

3. The toner according to claim 1 or 2, The toner, wherein the circularity of the silica particles is 0.95 or more.

4. The toner according to any one of claims 1 to 3, The toner is characterized in that the fine powder has a dispersion index of -10 or more.

5. The toner according to any one of claims 1 to 4, The toner, wherein the dispersion index of the silica particles is 25 or less.

6. The toner according to any one of claims 1 to 5, the content of the fine powder is 0.1 parts by mass or more and 5.0 parts by mass or less with respect to 100 parts by mass of the toner particles, The toner, wherein the content of the silica particles is 0.5 parts by mass or more and 4.0 parts by mass or less with respect to 100 parts by mass of the toner particles.

7. The toner according to any one of claims 1 to 6, The toner according to the present invention is characterized in that the molar ratio of silicon to titanium in the fine powder, Si / Ti, is 0.03 or more and less than 1.

0.

8. The toner according to any one of claims 1 to 7, The toner, wherein the toner particles are pulverized toner particles.

9. A method for producing the toner according to any one of claims 1 to 8, comprising the steps of: a first external addition step of mixing the fine powder with the toner particles to cause the fine powder to adhere to surfaces of the toner particles; a second external addition step of mixing the silica particles with the toner particles to cause the silica particles to adhere to the surfaces of the toner particles; A method for producing a toner, comprising the steps of: performing the first external addition step and then performing the second external addition step.

10. A method for producing the toner according to claim 9, a mixing rotation speed in the first external addition step being D and a mixing rotation speed in the second external addition step being E, wherein D / E is 1 or more.

11. A two-component developer comprising the toner according to claim 1 and a carrier.

12. An image forming apparatus using the two-component developer according to claim 11.

Citation Information

Patent Citations

  • Toner

    JP2015028601A

  • Toner

    JP2016102904A

  • Strontium titanate-based fine particle for toner and manufacturing method therefor

    JP2018020919A

  • Electrostatic charge image developer, process cartridge, image forming apparatus, and image forming method

    JP2020046578A

  • Toner, toner container, developer, developing device, process cartridge, and image forming device

    JP2020190724A